Leaderships and Participatory Processes: A Reflection on Democratic Citizenship - Nuno Fraga (Universidad Autónoma de Madrid, 2016)
This paper reflects on the potential of leadership in the strategic management of public space, particularly from the concerted dynamics of local government to the community. We propose a theoretical reflection on the leadership styles based on the thoughts of Daniel Goleman, converging on the need to understand such assumptions in the praxis of a Mayor. The case study sought to understand the channels of communication between leader and led, and then contextualize the importance of this theoretical framework in conducting participatory processes in local space; its relation to democratic citizenship and the place of education at the crossroads of a possible democracy. We conclude that the issues of power sharing and / or delegation interfere with the actual opening of stakeholders during the participatory processes, it is necessary to rethink the leadership of proximity as a key factor to the success of these practices.